569 Improving the Urology Post Take Ward Round with Best Clinical Practice and A Governance Checklist. Quality Improvement Project Within Belfast Health and Social Care Trust 2020. (4th May 2021) - McLoughlin, P; McAdam, A
Abstract: Introduction: The post take ward round (PTWR) is a vital element to ensure patient safety. Although well established as a necessity, often documentation is poor and does not accurately reflect a clinical assessment or generated management plan. This quality improvement project aimed to assess the pitfalls of the PTWR and improve these were possible in-line with best clinical practice. Method: Audit standards were established using national guidelines, including those by the Royal College of Physicians, Royal College of Surgeons, GAIN guidelines and NICE. An initial audit was carried out against these guidelines. Following this, three distinct interventions were implemented namely, Junior Doctor Education Sessions, a Urology Consultant Email Circular, and the development of a Urology PTWR Checklist. After each intervention, a re-audit was carried out. Results: Compliance with guidelines improved across all standards set. Overall compliance improved from 19.0% to 70.4% after our three interventions were implemented. Conclusions: The results of the initial audit outlined that PTWR documentation is often very poor or severely lacking. Fortunately, this QIP demonstrates how the urology PTWR can be significantly improved with relatively simple measures.